Shallow water tidal flat use and associated specialized foraging behavior of the great hammerhead shark (Sphyrna mokarran). Issue 4 (3rd July 2016) - Roemer, Robert P.; Gallagher, Austin J.; Hammerschlag, Neil
Abstract: Evidence suggests the great hammerhead shark, Sphyrna mokarran, is vulnerable to a variety of anthropogenic stressors, and is an understudied species of shark due to its cryptic nature and wide-ranging movements. While recognized as both a pelagic-coastal and a highly mobile predator, minimal anecdotal evidence exist describing shallow water habitat use by this species. This report describes six cases in which a great hammerhead shark utilizes an inshore shallow water flats environment (<1.5 m in depth), five of which involve prey capture. These observations permitted identification of two novel behaviors that may allow great hammerheads to inhabit these shallow habitats: a (1) prey-capture technique termed 'grasp-turning' that involves burst swimming at tight turning angles while grasping prey and (2) a post-predation recovery period whereby the shark maintains head-first orientation into the current that may facilitate respiration and prey consumption. These behavioral observations provide insights into the natural history of this species.